Closure and Attention Activation in Human Automatic Behaviour: A Framework for the Formal Analysis of Interactive Systems - Cerone, Antonio (Electronic Communications of the EASST, 2011)
Automatic behaviour can be defined as a fast processing human activity that does not require attention to occur. According to Norman and Shallice’s model of attention and automaticity the majority of responses are under fairly automatic control triggered by environmental cues. In this paper we define a process algebraic framework to formalise Norman and Shallice’s model and illustrate it through two case studies: Driving and using an Automatic Teller Machine (ATM). Finally we show how to use model-checking to analyse model instantiations and present the outcome of the analysis for the ATM case study.